PENGARUH EXPERIENTIAL MARKETING DAN BRAND TRUST TERHADAP CUSTOMER LOYALTY: (Studi Pada Konsumen Produk Wardah di Kecamatan Talaga) - Melia Wida Rahmayani; Wulan Riyadi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
ABSTRACT In the midst of intense competition for cosmetic products, the company tries to fulfill the need for cosmetics with various product innovations. This method is done by the company in addition to adding new customers, it also retains existing customers or known as consumer loyalty. This study aims to determine Experiential Marketing, Brand Trust and Customer Loyalty on consumers of Wardah products in Talaga district. In addition, the purpose of this paper is to find out how much influence Experiential Marketing and Brand Trust have on Customer Loyalty. The research method used is a survey method with a descriptive and verification approach. The population used is consumers of wardah products in the district of talaga, while the sample used is 100 samples. The sampling technique used is non-probability sampling with incidental sampling technique, the analysis used in this study is classical assumptions, multiple linear regression analysis, coefficient of determination, and hypothesis testing. For the t test using a partial hypothesis test and for the F test using a model feasibility test. The results show that Experiential Marketing has a significant effect on Customer Loyalty, Brand Trust has a significant effect on Customer Loyalty.